Migraine patients visiting Chinese medicine hospital: Protocol for a prospective, registry-based, real-world observational cohort study. - Shaohua Lyu; Claire Shuiqing Zhang; Anthony Lin Zhang; Jingbo Sun; Charlie Changli Xue; Xinfeng Guo (PLoS ONE, 2022)
Introduction Migraine is a disabling, recurrent headache disorder with complex comorbidities. Conventional treatments for migraine are unsatisfactory, with side effects and limited effectiveness. Chinese herbal medicine (CHM) has been used as an alternative or complementary treatment option for migraine in China. Currently, the existing evidence of benefit of CHM for migraine has been generated from randomised clinical trials using standardised intervention with a focus on internal validity hence with limited external validity. Moreover, CHM individualised intervention design, patients' preferences and concerns, and clinicians' experience are critical to clinical decision making and therapeutic success. This real-world observational study aims to gather practice-based evidence of effects and safety of CHM for migraine in the context of integrating Chinese medicine diagnostic procedures, patients' preferences and matters relevant to clinical decision making. Methods and analysis The study is being undertaken at the Guangdong Provincial Hospital of Chinese Medicine (GPHCM) from December 2020 to May 2022. We anticipate that approximately 400 adult migraineurs will be enrolled and observed on their migraine severity, analgesic consumption, quality of life, anxiety, depression and insomnia at baseline and then every four weeks over 12 weeks. Treatments, diagnostic information, and patient-reported most bothersome symptoms will be collected from patient clinical records. Patient's demographic data, preferences and concerns on CHM treatments will also be gathered at baseline and be analysed. Factors related to clinical outcomes will be explored with multiple correlation and multivariable regression analyses. Effects of CHM will be evaluated using generalised estimated equation, based on clinical outcome data. Discussion This study will provide comprehensive evidence of CHM for migraine in the context of evidence-based practice. Trial registration number ChiCTR2000041003.